Relationship between potential recruits from VET and HE : case studies from Germany, England and Switzerland - Hippach-Schneider, Ute [Verfasser]; Weigel, Tanja [Verfasser] (My University, 2013)
"The project involves an investigation of company recruitment strategies for intermediate level employees in three countries: Germany, England and Switzerland. It is conducted by the Federal Institute for Vocational Education and Training (BIBB) in cooperation with the University of Zurich. The reasons for recruitment decisions are investigated to shed light on which qualifications best cover the requirements companies have for certain activities. The objective is to identify the strengths and weaknesses of recruitment from vocational education and training (VET) compared to graduates for a certain activity profile as well as to facilitate discussion about equivalences between qualifications among the three countries. This chapter presents some results of the first project phase." (Autorenreferat, BIBB-Doku)
Keywords: S 5.3 Personalentwicklung; P 2.4 Facharbeiter / Gesellen; P 2.6 Hochschulabsolventen; I 2.2.1 Westeuropa; Personalgewinnung; Qualifikationsnachfrage; Ausbildungsabschluss; Bachelor; Unternehmen; Internationaler Vergleich; Schweiz; Bundesrepublik Deutschland; England